2010
DOI: 10.2353/ajpath.2010.090957
|View full text |Cite
|
Sign up to set email alerts
|

Flaky Tail Mouse Denotes Human Atopic Dermatitis in the Steady State and by Topical Application with Dermatophagoides pteronyssinus Extract

Abstract: The barrier abnormality, a loss-of-function mutation in the gene encoding filaggrin (FLG), which is linked to the incidence of atopic dermatitis (AD), is a recently discovered but important factor in the pathogenesis of AD. Flaky tail (Flg ft ) mice, essentially deficient in filaggrin, have been used to investigate the role of filaggrin on AD. However, the relevancy of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
126
4
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(140 citation statements)
references
References 40 publications
(61 reference statements)
7
126
4
3
Order By: Relevance
“…Therefore, filaggrin is absent from the cornified layers in the epidermis of the Flg ft mouse (Fallon, et al, 2009, Presland, et al, 2000, Scharschmidt, et al, 2009). Consistently, we and others have described that Flg ft mice express a truncated and smaller profilaggrin protein that is not processed to filaggrin (Fallon, et al, 2009, Moniaga, et al, 2010, Presland, et al, 2000 (Fig.1). Fig.…”
Section: Origin Of Flaky Tail Micesupporting
confidence: 55%
See 2 more Smart Citations
“…Therefore, filaggrin is absent from the cornified layers in the epidermis of the Flg ft mouse (Fallon, et al, 2009, Presland, et al, 2000, Scharschmidt, et al, 2009). Consistently, we and others have described that Flg ft mice express a truncated and smaller profilaggrin protein that is not processed to filaggrin (Fallon, et al, 2009, Moniaga, et al, 2010, Presland, et al, 2000 (Fig.1). Fig.…”
Section: Origin Of Flaky Tail Micesupporting
confidence: 55%
“…The first report showed only histological abnormality without clinical manifestation (Fallon, et al, 2009), and the second demonstrated spontaneous eczematous skin lesions after 28 weeks of www.intechopen.com age (Oyoshi, et al, 2009), and the third contained no notice of any spontaneous dermatitis in Flg ft mice (Scharschmidt, et al, 2009). The fourth paper by Moniaga et al have demonstrated that Flg ft mice showed spontaneous dermatitis with skin lesions mimicking human AD as early as 5 weeks of age with mild erythema and fine scales and the cutaneous manifestations advanced with age in a steady state under SPF conditions (Moniaga, et al, 2010) (Fig. 2).…”
Section: Flaky Tail Mouse In a Steady Statementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was shown by Moniaga et al that Flg-deficient mouse skin shows increased susceptibility to Dermatophagoides pteronyssinus-induced dermatitis, a pathogen relevant for human AD pathogenesis. 29 There may be different thresholds for movement of water versus other chemicals through the stratum corneum, eg, depending on lipophilicity.…”
Section: Discussionmentioning
confidence: 99%
“…mRNA was isolated using TRIzol (Invitrogen), according to the manufacturer's instructions. Quantitative RT-PCR was performed as described previously, using the housekeeping gene glyceraldehyde-3-phosphate dehydrogenase (GAPDH) as a control 50 .…”
Section: Bone Marrow Transplantation For Bm Transplantation Red Blomentioning
confidence: 99%